ChemInform Abstract: A Simple and Straightforward Approach Toward Selective C=C Bond Reduction by Hydrazine. Issue 16 (28th March 2013) - Chen, Hao; Wang, Jianmin; Hong, Xuechuan; Zhou, Hai‐Bing; Dong, Chune
Abstract 18 representative examples of the title reaction with C=C bonds in various steric and electronic environments are reported.